Effect of α-lipoic acid on immune parameters in rats (Experimental biology, 2016)
Nowadays the actual problems is to change the environment that violates human vital organs like the brain, heart, liver. Currently used in many products lipoic acid is widely used against intoxication. Lipoic acid with antioxidant properties to positively influence the organism tserroz hepatitis and liver play an important rule in lipid metabolism and choleretic, antispasmodic action and stands as building immunity. A lipoic acid also helps absorbed antioxidants (e.g., vitamins A and E) that were received in the body. Aim of this work to study the effect of α-lipoic acid on immune parameters.
Keywords: α- lipoic acid; rats; immunological parameters; initial form; control group.